2010
DOI: 10.3354/meps08693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on liver pathology and other diseases in flatfish: implications for assessment of marine ecological health status

Abstract: Age at disease onset, a familiar concept in human medicine, has not been commonly discussed in relation to diseases of wildlife. Furthermore, while age has been anecdotally linked with disease susceptibility in aquatic animals (e.g. in aquaculture), little attention has been devoted to health of specific cohorts in wild aquatic animal populations. In an attempt to refine current approaches to marine environmental monitoring programmes that utilise fish diseases as a sentinel for ecological status, we have inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
(58 reference statements)
1
32
0
Order By: Relevance
“…However, before such a conclusion can be drawn, more research and data analyses are required, e.g., in order to study possible age effects. For instance, from studies in wild flatfish, it is known that young age groups tend to have less neoplastic liver nodules than their conspecifics of higher age groups Stentiford et al, 2010). An alternative explanation of the absence of neoplasms could be given by the example of the starry flounder.…”
Section: Discussionmentioning
confidence: 98%
“…However, before such a conclusion can be drawn, more research and data analyses are required, e.g., in order to study possible age effects. For instance, from studies in wild flatfish, it is known that young age groups tend to have less neoplastic liver nodules than their conspecifics of higher age groups Stentiford et al, 2010). An alternative explanation of the absence of neoplasms could be given by the example of the starry flounder.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that colour pattern definition takes place at an early life stage and that, once established, the aberrant colour patterns are maintained through life. However, when Stentiford et al (2010) investigated the age at first occurrence of several disease conditions affecting dab in the North Sea and the Irish Sea where the smallest fish sampled were in the range of 10 to 14 cm (the majority of these being 1 yr old), the first occurrence of hyperpigmentation in North Sea dab was found to be at 3 yr . Similarly, data from a different area of the North Sea recorded the first occurrence of hyperpigmentation in 2 yr old dab, the smallest with 12 cm but higher prevalence observed in >15 cm fish (GrĂźtjen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers being either biochemical, physiological or histological are important to interpret the toxicity of the aquatic systems and have been widely used to assess environmental health (Myers et al, 1998;FracĂĄcio et al, 2003;Costa et al, 2009;Stentiford et al, 2010;Brooks et al, 2009;Hutchinson et al, 2013;Stentiford et al, 2014). Significantly a number of field, laboratory and mesocosm studies have also demonstrated causal links between exposure to chemical contamination and the development of toxicopathic hepatic lesions (Hinton and Lauren, 1990;Hinton et al, 1992;Myers et al, 1998;Stehr et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Thus histological and biochemical biomarkers provide a powerful tool for detection and characterisation of the biological end points of toxicant and carcinogen exposure (Hinton and Lauren, 1990;Hinton et al, 1992;Moore and Simpson, 1992). Furthermore, the utility of histopathology as a sensitive indicator of health in wild fish populations has been demonstrated in Europe and North America (Myers et al, 1998;Costa et al, 2009;Stentiford et al, 2009;Vethaak et al, 2009;Stentiford et al, 2010).…”
Section: Introductionmentioning
confidence: 96%